Assessing the potential impacts of climate change on droughts in East Africa using CORDEX-CORE regional climate models' simulations: A focus on Tanzania - SALAH, Mohamed; MOURSY, Fawzia; SOLIMAN, Eman; GAMAL, Gamil (Contributions to Geophysics and Geodesy, 2025)
This study used the Standardized Precipitation Index (SPI) to detect drought episodes in Tanzania, as well as their characteristics in terms of duration (years), severity, and intensity, and analyse their trends. To conduct the analysis, 12-month standardized precipitation was employed, utilizing historical data from 1970 to 2005 and future projections from 2021 to 2100 for ten meteorological stations in Tanzania. These historical projections are based on simulations generated by Coordinated Regional Climate Downscaling Experiment (CORDEX-CORE) models. According to projected future changes, precipitation would increase at 60% of stations, notably in Tanzania's eastern regions. The highlands, however, are predicted to experience a greater rise in precipitation than the desert and semi-arid areas, which are predicted to receive less precipitation. In addition, it is expected that in the mid-future, drought events will occur more frequently in Tanzania's dry regions and will last longer and be more severe. Based on the estimated SPI values, the Mann-Kendall (MK) test and Sen's slope estimator were used to examine the drought trend. The overall analysis of the computed SPI time series demonstrated that drought is more frequent and severe in Tanzania, especially in Kigoma, Songea and Tanga. Based on the SPI-12 values, the results show that the most prolonged and severe droughts occurred during the 2039–2041, 2045–2046, 2068–2072, 2081–2083 and 2092–2095 marking extremely dry years. To mitigate the potential impacts of climate change, it is crucial to implement adaptation measures that address the specific challenges faced by Tanzania.